Inventarisasi dan identifikasi ektoparasit yang menginfeksi benih ikan Nila (Oreochromis niloticus) - Massora Dudung; Reni L. Kreckhoff; Reiny A. Tumbol; Sammy N.J. Longdong; Winda M. Mingkid (Universitas Sam Ratulangi, 2023)
This study aimed to identify the parasites in tilapia seeds cultivated by the Matelenteng Fish Cultivation Group in Tumaluntung Village, as well as to analyze the prevalence, incidence, dominance index and preference level of parasites in tilapia seeds. This research was conducted from May to July 2023 in Tumaluntung Village, Kauditan District, North Minahasa Regency, North Sulawesi Province. Parasite examination was carried out on 15 samples of tilapia seeds which included the skin, fins, and gills of the fish. The fish samples were taken from the Matelenteng fish cultivation location in Tumaluntung Village, Kauditan District, North Sulawesi Province. The fish were taken from 1 breeding pond and put into plastic bags containing water, then given oxygen, and then brought to the Aquaculture Technology Laboratory of FPIK Unsrat for examination. Before the examination was carried out, the test fish were put into a bucket and given aeration so that the tilapia seeds remained alive until they were examined. Next, the length of the tilapia seeds was measured using a ruler. Examination of the tilapia seed samples was carried out using the smear preparation method where the examined organ was scraped, and the results of the scraping were placed in a Petri dish before being smeared on a prepared glass slide. Parasite examination was conducted using a microscope with a magnification of 100x. The inventory and identification results found 2 types of parasites, namely Epistylis sp. with 13 individuals in 3 samples of tilapia seeds and Dactylogyrus sp. with 2 individuals in 2 samples of tilapia seeds infecting the tilapia seeds. The prevalence rate of Epistylis sp. parasites was obtained at 33.33% or generally, there is a mild infection. Dactylogyrus sp. with a prevalence rate of 13.33% is classified as often infected with an incidence rate at a very mild level. The preference level of parasites obtained a value of X2 hit 3.74 < X2 tab 9.210 indicating a difference in the preference level of parasites in the tilapia seed body organs. Keywords: Ectoparasites, prevalence, incidence, preference level